Antibacterial bone adhesive cement for preventing sternal infections after cardiac surgery. Issue 10 (15th May 2023) - Pradeep, Aathira; Varma, Praveen Kerala; Arumugam, Thennavan; Vijayan, Anjaly Maravattikal; Vasudevan, Anil Kumar; Rangasamy, Jayakumar
Abstract: Deep Sternal wound infection (Mediastinitis) after cardiac surgery can be potentially caused by both Gram-positive and Gram-negative bacteria. The incidence of sternal infection appears to be on the rise in current practice and is associated with increased hospital stay, cost of care, and mortality. Due to the unmet need for mediastinitis treatment or prevention, we developed and characterized an antibacterial, biocompatible bone adhesive cement composed of tetracalcium phosphate, phosphoserine, and the antibacterial drugs, amikacin and vancomycin (TPAV). Vancomycin and amikacin show a continuous release pattern from TPAV for up to 60 and 90 days, respectively. In vitro and ex vivo analysis of TPAV's antibacterial properties shows inhibitory activity against the growth of Escherichia coli (E. coli), Klebsiella pneumoniae (K. pneumoniae) and Staphylococcus aureus (S. aureus), and their biofilm formation. TPAV is also capable of inhibiting the growth of E. coli, K. pneumoniae and S. aureus when grown together as co-culture. Furthermore, the in vivo studies are done in a rat sternotomy model infected with S. aureus and E. coli, and TPAV demonstrated significant inhibitory activity when compared to the infected control group. This study highlights the potential of the developed antibacterial bone adhesive cement for preventing mediastinitis in clinics.